Precursors of college students' attitudes towards cross-cultural collaboration: the role of group-learning activity design and openness to diversity. Issue 6 (3rd July 2022) - Alt, Dorit; Raichel, Nirit
ABSTRACT: The increasing calls for diversity research signal a need to redesign learning and teaching strategies and include appreciations of collaboration and diversity as part of the students' learning outcomes. However, changing the learning environment by incorporating innovative pedagogical techniques into multicultural learning environments is often fraught with difficulties, stemming partly from students' attitudes towards cross-cultural collaborative learning. The present sequential explanatory study sought to design a collaborative group-learning activity and measure its effect on students' attitudes towards collaborative learning by using a pre/post intervention design. Another aim was to explore the role of students' openness to diversity and challenge in explaining these attitudes. Data were gathered from 84 first-year Israeli Arab and Jewish students by three questionnaires: Constructivist Learning in Higher Education Settings, Openness to Diversity and Challenge scale, and Students' Attitude towards Collaborative Learning, in addition to semi-structured interviews. Findings showed that the Jewish students' positive attitudes towards collaborative learning have decreased between the tests (after the collaborative activity). The empirical model, designed by Partial Least Squares – Structural Equation Modelling (PLS-SEM), indicated a direct contribution of students' positive perception of the collaborative activity to their attitudes towards collaborative learning above cultural differences. Arab students' proclivity towards openness to diversity enhanced their positive attitudes towards collaborative learning. The students of both cultures described in their own words the group dynamics throughout the activity. Qualitative analysis of their interviews revealed several explanations related to students' experienced challenges during the collaborative activity. Recommendations for mitigating these challenges are provided.